INITIAL EXPERIENCE OF PERCUTANEOUS NEPHROLITHOTOMY IN HAZARA REGION - Malik, Masood Akhtar; Jamil, Muhammad Nasir; Farooq, Umar; Mahmood, Malik Furqan (Journal of Ayub Medical College Abbottabad, 2018)
Background: Renal stone disease affects a large population of the world and surgical management is the main stay treatment for larger stones. In comparison to open procedures, percutaneous nephrolithotomy (PCNL) has been known to offer almost similar stone clearance with least patient morbidity. The study was done with the objectives to evaluate our initial experience of PCNL in the management of nephrolithiasis in Abbottabad. Methods: A case series study was carried out at a private hospital, Valley Medical Complex, Abbottabad, including the 35 patients undergoing PCNL from January 2015 to February 2016. Results: 35 patients (23 male (65.7%) and 12 female (34.3%) underwent PCNL with a mean age of 35.57 years±6.701 and mean renal stones size of 24.49 mm±7.098. 28.6% stones (n=10) were located in the renal pelvis, 28.6% (n=10) in the lower pole of kidney and 42.9% (n=15) had stones in other sites of kidney. 25.7% patients (n=9) had mild, 57.1% (n=20) moderate and 17.1% (n=6) had gross hydronephrosis. 28.6% patients (n=10) had a single renal stone, 61.4% (n=18) had ‰¥2 stones whereas 7 patients (20%) had partial stag horn stone. Tract access was gained through upper pole in 8.6% patients (n=3), middle pole in 11.4% (n=2), and lower pole in 85.7% (n=30). Complete stone clearance was achieved in 30 patients (85.7%) whereas partial clearance accomplished in 3 patients (8.6%). 2 patients had PCNL failure due to failed tract access. Postoperatively 10 patients (28.6%) had significant pain, 06 patients (17.1%) had fever and 01 patients (2.9%) required blood transfusion. Conclusions: PCNL is a safe procedure for management of upper urinary tract stones and is still in evolution stages in Hazara region. Keywords: renal stones; percutaneous nephrolithotomy (PCNL); hazara; staghorn stone